Traumatic states : gendered violence, suffering, and care in Chile - Parson, Nia, 1973- (Vanderbilt University Press, 2013)
The end of the Pinochet regime in Chile saw the emergence of an organized feminist movement that influenced legal and social responses to gender-based violence, and with it new laws and avenues for reporting violence that never before existed. What emerged were grassroots women's rights organizations, challenging and engaging the government and NGOs to confront long-ignored problems in responding to marginalized victims. The author, an anthropologist, explores the development of methods of care and recovery from domestic violence.